Slide Show : projected images in contemporary art - Alexander, Darsie; Anastas, Rhea; Bolger, Doreen; Collins, Thom; Harrison, Charles; Little, David; Storr, Robert; Warnock, Molly (Baltimore London : Baltimore Museum of art Baltimore Tate Publishing London, 2005)
Barry, Robert ; Baumgarten, Lothar ; Broodthaers, Marcel ; Coleman, James ; Dibbets, Jan ; Doherty, Willie ; Fischli & Weiss ; Floyer, Ceal ; Goldin, Nan ; Graham, Dan ; Lawler, Louise ; Levitt, Helen ; Melchert, James ; Mendieta, Ana ; Monk, Jonathan ; Oppenheim, Dennis ; Smith, Jack ; Smithson, Robert ; Wodiczko, Krzysztof
bibliog. p. 153-159
This volume has been published in conjunction with the exhibition SlideShow, organized by The Baltimore Museum of Art, Baltimore, Maryland, and held at: The Baltimore Museum of Art, 27.02.2005 - 15.05.2005; Contemporary Arts Center, Cincinnati, 02.07.2005 - 11.09.2005; The Brooklyn Museum of Art, 07.10.2005 - 08.01.2006
Engels
boek